Pengaruh Alat Permainan Lego Terhadap Perkembangan Kognitif Anak Usia Dini 4-5 Tahun di PAUD Arriyadatul Badi’ah - Dewi Lestari; Mariyani Mariyani (Universitas Malahayati Lampung, 2024)
ABSTRACT According toWHO in 2021 reported that 5-25% of young children suffer from minor brain dysfunction, including impaired fine motor development (WHO, 2021). To determine the effect of educational game toolsLego on cognitive development in Early Childhood (4-5 Years) in Earlyyadul Badi'ah PAUD Kab. Karawang in 2023. Musequasi experimental with a planThe one group pretest-posttest design. The study population was 4-5 years old children who took part in learning activities at the Arriyadul Badi'ah PAUD, totaling 40 children. The sampling technique uses total sampling. Analyst bivariate use testWilcoxcone. The results of the Paired sample t test obtained a significance value of 0.000 0.05 so it can be concluded that there is an influence of lego games on the cognitive development of early childhood (4-5 years) in Earlyyadul Badi'ah PAUD Kab. Karawang. It can be concluded that lego games have an effect on the cognitive development of early childhood (4-5 years) at the Arriyadul Badi'ah PAUD, Kab. Karawang. DisThe recommendations in this study are for educational institutions, for research sites, for respondents and for future researchers. Keywords: Lego Games, Cognitive Development, Early Childhood. ABSTRAK Menuruut WHO tahun 2021 melaporkan bahwa 5-25% dari anak-anak usia dini menderita disfungsi otak minor, termasuk gangguan perkembangan motorik halus. Untuk mengetahui pengaruh alat permainan edukatif Lego terhadap perkembangan kognitif pada Anak Usia Dini (4-5 Tahun) di PAUD Arriyadul Badi’ah Kab. Karawang Tahun 2023. Menggunakan quasi eksperimental dengan rancangan The one group pretest-posttest design. Populasi penelitian adalah anak usia 4-5 tahun yang mengikuti kegiatan belajar di PAUD Arriyadul Badi’ah berjumlah 40 anak. Teknik pengambilan sampel menggunakan total sampling. Analis bivariate menggunakan uji Wilcoxcone. Hasil Uji Paired sampel t test diperoleh nilai signifikansi sebesar 0,0000,05 sehingga dapat disimpulkan terdapat pengaruh permainan lego terhadap perkembangan kognitif anak usia dini (4-5 Tahun) Di PAUD Arriyadul Badi’ah Kab. Karawang. Simpulan di dapatkan permainan lego berpengaruh terhadap perkembangan kognitif anak usia dini (4-5 Tahun) Di PAUD Arriyadul Badi’ah Kab. Karawang. Disaran dalam penelitian ini untuk Institusi pendidikan, untuk tempat penelitian, untuk responden dan untuk peneliti selanjutnya. Kata Kunci: Permainan Lego, Perkembangan Kognitif, Anak Usia Dini